Korelasi Penggunaan Media Sosial dan Pola Tidur Mahasiswa UIN Sunan Gunung Djati - Inda Maula Zulfa; Ajeng Saeful Putri; Sulthon Ahmad Nawawi; Ghefira Rahima; Mia Lasmi Wardiyah (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
The rapid growth of social media among university students raises concerns regarding its impact on health, particularly sleep patterns. This research investigates the link involving social media usage intensity and students’ sleep patterns. A descriptive quantitative approach was employed through a survey method involving 30 active undergraduate students from various universities in Indonesia, using a survey based on Likert items. The analysis applied Pearson’s correlation to assess the intensity and orientation of the link between variables. The results revealed a strong and affirmative link between social media engagement and sleep pattern disturbances, indicated by a correlation score of 0.655. This reflects that greater intensity in using social media is associated with increased likelihood of disrupted sleep patterns, including irregular sleep schedules, reduced sleep duration, and decreased sleep quality. These findings emphasize the importance of better digital time management and educational interventions regarding healthy sleep habits, both for students and higher education institutions.